A Single Motion Chip for Multi-Motor EV Control - Ricardo de Castro (2010)
This article presents a single motion chip solution for controlling the powertrain of a multimotor electric vehicle (EV). The control chip is based on a FPGA (Field-Programmable Gate Array) module and features multi-motor control, strategies to increase the energy efficiency and reconfigurability to handle different powertrain configurations. In order to improve the EV safety a sliding mode traction controller (TC) was developed, ensuring robustness to parametric and modeling uncertainties. The TC was integrated in the motion chip, and uses exclusively the electric motors to maximize the transmission of longitudinal force under acceleration and light braking maneuvers. The TC's performance was experimental verified on a multi-motor EV prototype, demonstrating satisfactory competence in preventing excessive tire slip, particularly under low friction coefficient conditions.